1989
DOI: 10.1126/science.2531920
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of nef on HIV Replication: Implications for Viral Pathogenesis in the Host

Abstract: Stable lymphoid cell lines expressing the human immunodeficiency virus type 1 (HIV-1) nef gene product, p27, were established. The presence of p27 in the lymphoid cells suppressed replication of some strains of both HIV-1 and HIV-2. This observation indicates that nef could be important in the establishment of HIV latency. In contrast, fast replicating and highly cytopathic HIV-1 isolates recovered from patients with advanced disease states were not affected by the negative effect of nef present in these lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
4

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(102 citation statements)
references
References 22 publications
3
95
0
4
Order By: Relevance
“…The most obvious product of the PCR analysis represented nefmRNA. This was surprising in view of the putative role of nef as a factor that negatively regulates viral transcription in some (Fisher et al, 1986;Luciw et al, 1987;Ahmad & Venkatesan, 1988;Cheng-Mayer et al, 1989;Niederman et al, 1989) but not all studies (Kim, 1989b). Using a similar PCR system for detecting spliced HIV-1BaL mRNAs in macrophages (but without conducting a time-course analysis), Robert-Guroff et al (1990) also found a strong nefmRNA signal in macrophages that had been infected with HIV-IBaL for 12 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious product of the PCR analysis represented nefmRNA. This was surprising in view of the putative role of nef as a factor that negatively regulates viral transcription in some (Fisher et al, 1986;Luciw et al, 1987;Ahmad & Venkatesan, 1988;Cheng-Mayer et al, 1989;Niederman et al, 1989) but not all studies (Kim, 1989b). Using a similar PCR system for detecting spliced HIV-1BaL mRNAs in macrophages (but without conducting a time-course analysis), Robert-Guroff et al (1990) also found a strong nefmRNA signal in macrophages that had been infected with HIV-IBaL for 12 to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 nef gene encodes a protein with an apparent molecular mass of 24-27 kDa, which is myristoylated (Allan et al, 1985;Guy et al, 1987). The biological function of Nef is not yet clear, however, it can be regarded as conclusive that it is not a guanine-nucleotide-binding protein (Kaminchik et al, 1990;Nebreda et al, 1991Nebreda et al, , 1992Matsuura et al, 1991;Backer et al, 1991;Harris et al, 1992;Wolber et al, 1992) participating in cellular signaling pathways as has been claimed by some authors (Samuel et al, 1987;Guy et al, 1987;Cheng-Mayer et al, 1989). Nef is mainly localized in the cytoplasm associated with cellular membranes, but it is also found in the nucleus (Franchini et al, 1986;Kienzle et al, 1992a,b;Ovod et al, 1992;Yu and Felsted, 1992;Kohleisen et al, 1992).…”
mentioning
confidence: 97%
“…It is highly conserved in all primate lentiviruses, suggesting that its function is essential for survival of these pathogens. Nevertheless, early publications reported a negative effect of Nef on viral replication, hence the name 'negative factor' or Nef [93,94]. Subsequent studies, however, demonstrated that Nef plays an important role in several steps of HIV replication.…”
Section: Negative Regulator Factor(nef)mentioning
confidence: 99%